Livres reçus (Cahiers du monde russe, 2017)
ANTONOV Sergei, Bankrupts and Usurers of Imperial Russia : Debt, Property, and the Law in the Age of Dostoevsky and Tolstoy, Cambridge MA – Londres : Harvard University Press, 2016, 388 p., index, ill. BROOKS PLATT Jonathan, Greetings Pushkin : Stalinist Cultural Politics and the Russian National Bard, Pittsburgh PA :University of Pittsburgh Press (Pitt Series in Russian and East European Studies), 2016, 366 p., index, bibliogr., ill. BRUNO Andy, The Nature of Soviet Power : An Arctic Environ.